2021
DOI: 10.1007/s00259-021-05378-0
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-FAPI-PET/CT in patients with various gynecological malignancies

Abstract: Purpose 68Ga-FAPI (fibroblast activation protein inhibitor) is a novel and highly promising radiotracer for PET/CT imaging. The aim of this retrospective analysis is to explore the potential of FAPI-PET/CT in gynecological malignancies. We assessed biodistribution, tumor uptake, and the influence of pre- or postmenopausal status on tracer accumulation in hormone-sensitive organs. Furthermore, a comparison with the current standard oncological tracer 18F-FDG was performed in selected cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 38 publications
9
111
0
5
Order By: Relevance
“…An investigation of various malignancies including breast cancer (n = 14), ovarian cancer (n = 9), cervical cancer (n = 4), endometrial cancer (n = 2), leiomyosarcoma of the uterus (n = 1) and tubal cancer (n = 1) described impressive SUV metrics and TBRs and was equal or superior to FDG. Furthermore, immunohistochemistry staining demonstrated a strong FAP expression in ovarian cancer, breast cancer and leiomyosarcoma of the uterus, which is in concordance with previous studies [74]. With respect to ovarian cancer, FAPI-PET/CT might be of particular interest as preceding studies determined its presence in 97% of all ovarian cancers and showed a correlation between FAP and a poor clinical prognosis, chemotherapy resistance and shorter time until recurrence [4,[118][119][120][121][122].…”
Section: Gynecological Malignanciessupporting
confidence: 86%
See 2 more Smart Citations
“…An investigation of various malignancies including breast cancer (n = 14), ovarian cancer (n = 9), cervical cancer (n = 4), endometrial cancer (n = 2), leiomyosarcoma of the uterus (n = 1) and tubal cancer (n = 1) described impressive SUV metrics and TBRs and was equal or superior to FDG. Furthermore, immunohistochemistry staining demonstrated a strong FAP expression in ovarian cancer, breast cancer and leiomyosarcoma of the uterus, which is in concordance with previous studies [74]. With respect to ovarian cancer, FAPI-PET/CT might be of particular interest as preceding studies determined its presence in 97% of all ovarian cancers and showed a correlation between FAP and a poor clinical prognosis, chemotherapy resistance and shorter time until recurrence [4,[118][119][120][121][122].…”
Section: Gynecological Malignanciessupporting
confidence: 86%
“…Hormone-responsive organs seem to be associated with an increased uptake on FAPI-PET/CT. In an analysis regarding FAPI uptake in the breast, ovary and uterus, statistically significant differences were seen in the breast and ovaries with a stronger uptake in premenopausal patients [74]. Additionally, the uptake might correlate with the menstrual cycle.…”
Section: Hormone-responsive Organsmentioning
confidence: 96%
See 1 more Smart Citation
“…This indicates that approximately 7000 rare diseases have an impact on about 30 million people in the EU, highlighting the importance of a reliable and accurate staging tool despite low incidences [1]. A novel nuclear tracer, fibroblast activation protein inhibitor (FAPI), presented highly promising results in previously published analyses for imaging different types of cancer [2][3][4]. FAP, a cell membrane-bound type II serine protease, is overexpressed by cancer-associated fibroblasts (CAFs) which are associated with cancer-promoting processes and poor prognosis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…FAP imaging using [ 68 Ga]Ga-FAPI PET/CT was further investigated in multiple sarcomas [ 139 ], gynecological tumors [ 140 ], and pancreatic ductal adenocarcinomas (PDAC) [ 141 ]. These preliminary clinical data also suggest that FAPI ligands may have the potential to highly contribute to the diagnosis and potential therapy of those types of cancer; however, larger comprehensive studies are required for confirmation.…”
Section: Clinical Studies Of Radiolabeled-based Fap Inhibitorsmentioning
confidence: 99%